EFL Students’ Strategy in Reading English Text in Perspective Automatic Information Processing (AIP) - Resyi Fatmawati; Yousef Bani Ahmad; Sumarta Sumarta (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2021)
Currently, students are asked to be able to understand literacy in reading. However, to understand literacy, of course, it has to go through the right strategy especially to beginner reader students. The purpose of this study is to determine the strategy of students in reading English text through perspective from automatic information processing (AIP) in reading. The method for this study used interviews and observations of one participant conducted in the second-level high school. This study also uses descriptive case study as research design. This study shows 5 things that should be reviewed in reading English text, namely attention, decoding, comprehension, switching in reading and automaticity. However, the five things found in this study are still rarely noticed. Therefore, this study also aims to allow educators and students to know what steps to do as a strategy to be able to read and understand the text of reading in English especially for beginner reader.